RECOVERY MARKETING STRATEGY FOR CUSTOM BAG PRODUCER-HOME INDUSTRY DURING THE COVID-19 PANDEMIC - Purwanto Purwanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The covid-19 pandemic has a significant impact on various sectors in Indonesia, including creative industry sector. This research aims at describing recovery marketing strategy during the Covid-19 pandemic carried out by custom bag producer-home industry located at Mojolaban District, Sukoharjo Regency, Central Java, Indonesia. This study used a qualitative and descriptive method with documentation, observation, interview as techniques for collecting data. The research findings show that the recovery marketing strategy during the Covid-19 pandemic can be done through segmenting, targeting, and positioning to attract consumers. In addition, the supporting factors to run entrepreneurship efficiently and effectively are promotion through online media, partnerships, excellent service, and awarding. Keywords: Recovery marketing strategy, custom bags, covid-19 pandemic